Shedding light on the migratory patterns of the Amazonian goliath catfish, Brachyplatystoma platynemum, using otolith 87Sr/86Sr analyses. Issue 3 (15th February 2019) - Hauser, Marília; Doria, Carolina R.C.; Santos, Roberto V.; García‐Vasquez, Aurea; Pouilly, Marc; Pécheyran, Christophe; Ponzevera, Emmanuel; Torrente‐Vilara, Gislene; Bérail, Sylvain; Panfili, Jacques; Darnaude, Audrey; Renno, Jean‐François; et al.
Abstract: In the Amazon, migratory catfishes of the genus Brachyplatystoma are apex predators that are important for fisheries and conservation. The life cycle of Brachyplatystoma platynemum Boulenger, 1898 is poorly known, although it has been hypothesized to be very similar to that of Brachyplatystoma rousseauxii Castelnau, 1855, which uses the entire length of the Amazon basin to complete its life cycle (from the Andes to the estuary). This study provides the first data on the migratory patterns of B. platynemum at the individual level using otolith microchemistry. In total, 94 individuals were sampled close to major breeding areas in the Amazon basin (78 fish from the middle and upper Madeira River and 14 fish from the upper Amazon), and their lifetime movements were assessed by measuring variations in 87 Sr/ 86 Sr along transverse sections of their otoliths (ear stones), using laser ablation multi‐collector mass spectrometry (LA‐MC‐ICP‐MS). The migrations of B. platynemum are not as extensive as those of B. rousseauxii, and do not involve natal homing. Furthermore, the estuary is not a nursery area, at least for fish hatched in the Madeira. Nevertheless, B. platynemum migrates several thousand kilometres within the Amazon basin, with transboundary displacements between at least Bolivia, Brazil, and Peru. Current and planned hydroelectric development in the Amazon basin will severely disrupt both migration and access to breeding grounds, ultimately affecting the recruitment and population dynamics of these apex predators. The conservation of B. platynemum is crucial for the stability of the Amazonian aquatic food webs. This requires building effective fish passage on the two existing Madeira dams and considering alternative options to the large‐scale hydropower development in the Amazon basin.